Investigation of structural, morphological and antimicrobial properties of polyindole/Ag doped CeO2 nanocomposites. (2020) - Elango, M.; Deepa, M.; Subramanian, R.; Saraswathy, G.
Abstract: Silver doped cerium oxide nanocomposites were prepared at nitrogen atmosphere using polyindole as reducing agent (Polyindole/Ag-CeO2 ). The samples were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction study (XRD), scanning electron microscopy coupled with energy dispersive X-ray diffraction (SEM-EDAX), transmission electron microscopy (TEM). The FTIR study revealed the formation of polyindole/Ag-CeO2 nanocomposites. The XRD analysis confirmed the amorphous nature of nanocomposites. The porous structure of the polyindole and spherical shape of the Ag and CeO2 present in the nanocomposites were confirmed by SEM and TEM images. The prepared nanocomposites showed moderate antibacterial and antifungal activities.